Produksi Film Pendek “In Solo” Berbasis Multimedia - Indra Irawan (Indonesian Journal of Networking and Security (IJNS), 2014)
ABSTRACT : The development of cinema at the University of Surakarta now had enough amount with the theme of the movie is varied, there are themed documentary, romance, education, and others. Movie called "In Solo" itself tells of a young man who likes adventure by riding his beloved Vespa. The problem is how to make a short movie production or cinema which interesting and educating the media and used as a promotional icon city. Authors use research methods such as: literature, observation, interviews, design and implementation, Documentation. Formulation of cinema production step process consisting of Pre-Production, Production and Post Production. Short Movie Production "In Solo" Based Multimedia is expected to be a reference and information in producing cinema or movie, as aproof of the application of IT multimedia science. Keywords: Short Movie Production, Multimedia ABSTRAKSI: Perkembangan perfilman di Universitas Surakarta sekarang sudah cukup banyak dan variatif dengan tema film yang bermacam-macam, ada yang bertemakan dokumenter, percintaan, edukasi, dan lain-lain. Film berjudul “In Solo” sendiri menceritakan tentang seorang laki-laki muda yang suka berpetualang dengan mengendarai vespa kesayangannya. Adapun masalahnya adalah bagaimana membuat sebuah produksi sinema atau film pendek yang menarik dan mendidik yang sekaliguas digunakan sebagai media promosi icon kota. Metode penelitian yang penulis pergunakan adalah : kepustakaan, observasi, wawancara, perancangan dan implementasi, Dokumentasi. Perumusan langkah produksi sinema terdiri dari proses Pra Produksi, Produksi, dan Pasca Produksi. Produksi Film Pendek “In Solo” Berbasis Multimedia diharapkan dapat menjadi referensi dan informasi dalam memproduksi sinema atau film, sebagai suatu bukti penerapan ilmu IT multimedia. Kata Kunci : Produksi Film Pendek, Multimedia